Differential algebraic systems: Analysis and control - Salamanca, Juan Mauricio; Higuera-Martínez, Oscar Iván; Ramiréz, José Miguel (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2007)
It describes the fundamentals and principal aspects of the Linear Differential and Algebraic Systems (DAES), with respect to the dynamic systems Controllability, Observability, Stability and Admissibility. An Power electric system example is shown and analyzed at the end of this paper.